Раскройте скобки и привидите подобные слагаймые 2(х+4)-3(2-х)-х-4 х+1-5(2-+1)х-5 х+3-(2-х)-х-4 4(х+-х)-х-4 3(х-3)-4(1-+3)х-1 5(х+5)-4(1-+3)х-1

06Loki90 06Loki90    3   24.09.2019 02:50    0

Ответы
balatzkymaxp0a4t7 balatzkymaxp0a4t7  08.10.2020 13:57
2(х+4)-3(2-х)-х-4 = 2x + 8 - 6 + 3x - x - 4 = 4x - 2

х+1-5(2-х)-(5+1)х-5 = x + 1 - 10 + 5x - 6x - 5 = -14

х+3-(2-х)-х-4 = x + 3 - 2 + x - x - 4 = x - 3

4(х+3)-(5-х)-х-4 = 4x + 12 - 5 + x - x - 4 = 4x + 3

3(х-3)-4(1-х)-(4+3)х-1 = 3x - 9 - 4 + 4x - 7x - 1 = -14

5(х+5)-4(1-х)-(4+3)х-1 = 5x + 25 - 4 + 4x - 7x - 1 = 2x + 20
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика